2005
DOI: 10.1073/pnas.0508728102
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Bacillus subtilis anti-TRAP protein, an antagonist of TRAP/RNA interaction

Abstract: In Bacillus subtilis the anti-TRAP protein (AT) is produced in response to the accumulation of uncharged tRNA Trp . AT regulates expression of genes involved in tryptophan biosynthesis and transport by binding to the tryptophan-activated trp RNA-binding attenuation protein (TRAP) and preventing its interaction with several mRNAs. Here, we report the x-ray structure of AT at 2.8 Å resolution, showing that the protein subunits assemble into tight trimers. Four such trimers are further associated into a 12-subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 49 publications
(81 reference statements)
4
27
0
Order By: Relevance
“…The R32 crystal structure is essentially identical to the model in P6, even though the TRAP used was clearly purified as an 11-mer ring. Both crystal structures described here are entirely different from previously proposed models of the TRAP-AT interaction based on analytical centrifugation (12) and crystallography (13).…”
Section: Resultsmentioning
confidence: 45%
See 3 more Smart Citations
“…The R32 crystal structure is essentially identical to the model in P6, even though the TRAP used was clearly purified as an 11-mer ring. Both crystal structures described here are entirely different from previously proposed models of the TRAP-AT interaction based on analytical centrifugation (12) and crystallography (13).…”
Section: Resultsmentioning
confidence: 45%
“…Experimental tests of the current model (13) are, however, highly desirable, because there is no ready explanation for the ability of AT to compete with RNA binding to TRAP. This lack of mechanistic understanding is rather unusual in such a well-studied system, and we have addressed this issue with a variety of biophysical methods including crystallography.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Crystallographic studies of Bsu AT revealed a dodecamer (AT 12 ) comprising a tetrameric arrangement of trimers (AT 3 ). Each trimer is constructed around a three-helix bundle involving the C-terminal residues, and four trimers assemble to form the dodecamer through interactions in the zinc-binding and N-terminal regions (21). Notably, neither oligomeric form of AT, trimer or dodecamer, shares symmetry elements with its physiological target: undecameric TRAP.…”
mentioning
confidence: 99%